Factors Influencing Student’s Personal Financial Management at Nahdlatul Ulama Surabaya University In 2023 - Muttaqin, Ninnasi; Riadi, Hananda Aulia (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2023)
Personal financial management that is carried out from the start can make students achieve financial success quickly that leads to achieve a better life. This study aims to determine these factors; financial literacy, lifestyle, parental income, love of money, locus of control, and financial self-efficacy on personal financial management. The subject of this study was students of Nahdlatul Ulama Surabaya University. The research method used was quantitative with purposive sampling technique. The data used in this study was primary data with a questionnaire method that’s distributed to respondents. Data analysis using multiple linear regression analysis. This study provided result that partially there’s a significant effect of financial literacy, parental income, love of money, and financial self-efficacy on personal financial management. Beside that, this study also found that partially lifestyle and locus of control had no significant effect on personal financial management.